Spectrally and Spatially Tunable Terahertz Metasurface Lens Based on Graphene Surface Plasmons - Wei Yao; Linlong Tang; Jun Wang; Chunhui Ji; Xingzhan Wei; Yadong Jiang (IEEE Photonics Journal, 2018)
In this paper, we propose a spectrally and spatially tunable terahertz metasurface lens based on the surface plasmons of graphene ribbons. By tuning the graphene Fermi energy, the optical property of graphene surface plasmons can be dynamically modulated, leading to tailored abrupt phase shifts of the reflected light. We demonstrate a resulting large spectral tuning range from 4 to 6 THz for the proposed metasurface lens with a spatially adjustable focal point in tens of micrometers. The influence of electron relaxation time of graphene and thickness of ion-gel on the performance of the metasurface lens is also discussed. Such a terahertz metasurface lens with a large spectral and spatial tunability is expected to show the great potentials in realizing active terahertz elements.